2004
DOI: 10.1002/eji.200324797
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipase A2 induces dendritic cell maturation

Abstract: High level of phospholipase A2 (PLA2) activity is found in serum and biological fluids during the acute‐phase response (APR). Extracellular PLA2 in fluids of patients with inflammatory diseases such as sepsis, acute pancreatitis or rheumatoid arthritis is also associated with propagation of inflammation. PLA2 activity is involved in the release of bothpro‐ and anti‐inflammatory lipid mediators from phospholipids of cellular membranes or circulating lipoproteins. PLA2 may thus generate signals that influence im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…Mast cell-derived exosomes trigger functional maturation of dendritic cells ( 6 ). This maturation process involves secreted PLA 2 ( 13 ) and prostaglandins ( 14 ). Therefore, we investigated the presence of lipid-related proteins and lipid mediators on exosomes derived from the mast cell line RBL-2H3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell-derived exosomes trigger functional maturation of dendritic cells ( 6 ). This maturation process involves secreted PLA 2 ( 13 ) and prostaglandins ( 14 ). Therefore, we investigated the presence of lipid-related proteins and lipid mediators on exosomes derived from the mast cell line RBL-2H3.…”
Section: Discussionmentioning
confidence: 99%
“…The DC maturation process has been shown to involve lysophosphatidylcholine and secreted PLA 2 ( 13 ), and prostaglandins ( 14 ). We previously reported that exosomes from RBL-2H3 cells contain a high amount of lysophosphatidylcholine (LPC) ( 15 ) and that phospholipase D was involved in exosome release ( 16 ).…”
mentioning
confidence: 99%
“…During the APR, increased oxidation of LDL and secretion of PLA 2 both favour the production of LPC and other biologically active lipids that have the ability to stimulate DC maturation [8,46]. Elevated levels of active LPC in the blood can result from oxidation or PLA 2 hydrolysis of PC from lipoproteins accompanied by a decrease in the concentration of LPC inhibitors, albumin and native LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Certain PLA 2 groups also impact the adaptive immune system through the ability to activate signaling pathways that result in the generation of cytokines (94,97). The maturation of dendritic cells (DCs) from monocytes has been demonstrated to occur as a result of treatment with group III sPLA 2 s (94, 97).…”
Section: Spla 2 Smentioning
confidence: 99%